Genetic Basis of Brugada Syndrome - Xianghuan Xie; Yanghui Chen; Zhiqiang Li; Yang Sun; Guangzhi Chen (Biomedicines, 2025)
Brugada syndrome is a rare inherited heart disease characterized by ventricular arrhythmias and characteristic ST segment elevation, which increases the risk of sudden death. Studies have shown that the pathogenesis of this disease involves a variety of gene mutations, including abnormal functions of sodium, calcium, and potassium ion channels, resulting in cardiac electrophysiological disorders. These variants affect excitability and conduction of cardiomyocytes, thereby increasing the susceptibility to ventricular arrhythmias and sudden death. However, many genetic variants remain of uncertain significance or are insufficiently characterized, necessitating further investigation. This review summarizes the genetic variants associated with Brugada syndrome and discusses their potential implications for improving diagnosis and therapeutic approaches.